Managing a Shared Collection in a Changing World - Revitt, Matthew (Maine Policy Review, 2024)
The author of this commentary describes the Maine Shared Collections Cooperative and its efforts to address members' concerns about their commitments as library needs and functions change.
Keywords: libraries; shared collections; shared print